Proses Kerja Editor Media Sosial Fatiya Catering Sebagai Media Promosi - ibrahim, Mochammad Rafi; Saleh, Amiruddin (Asosiasi Ide Bahasa Kepri, 2025)
The rapid development of digital media has transformed how companies communicate with their audiences, including those in the catering industry. Fatiya catering, as a professional catering provider, utilizes social media particularly Instagram and TikTok as its main platform for promotion and customer engagement. This study aims to analyze the workflow of social media editors and the role of video content in supporting Fatiya catering’s digital marketing strategy. This research applies a qualitative descriptive method with data collected through observation, participation, interviews, and literature study conducted at Fatiya catering, Bogor City. The findings show that the editor’s workflow consists of three stages: pre production, production, and post production. The pre production stage involves concept planning based on event themes; the production stage includes real-time photo and video documentation; and the post-production stage focuses on editing using CapCut, Adobe Premiere Pro, Canva, and Adobe Photoshop to produce engaging and professional content. Video content plays a crucial role in enhancing Fatiya catering’s digital marketing by showcasing service quality, event atmosphere, and brand professionalism. The study concludes that effective teamwork, creativity, and continuous improvement in editing and storytelling are essential to strengthen brand image and promotional effectiveness.